2022
DOI: 10.3389/feduc.2022.942272
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a translation training program on English as a foreign language trainees’ translation skills

Abstract: This study aimed to measure the effectiveness of a training experience involving a simulation of the work environment in developing the translation skills of a group of translation trainees. It also sought to investigate the participants’ views about their training experience, as well as measure their level of satisfaction with the program. Thirty participants with qualifications in English language and translation from different regions of the Kingdom of Saudi Arabia participated in this study. This research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…As a result, neither in theory nor in the practice of translation there is a clear and holistic idea of what it is. The data we obtained concerning students' lack of knowledge of lexical units denoting concepts in this area are consistent with the opinion of Alolaywi [46], who studied the difficulties of translating English business vocabulary using experimental material. Alolaywi's study concludes that a certain number of errors in the translation of BC is acceptable.…”
Section: Discussionsupporting
confidence: 87%
“…As a result, neither in theory nor in the practice of translation there is a clear and holistic idea of what it is. The data we obtained concerning students' lack of knowledge of lexical units denoting concepts in this area are consistent with the opinion of Alolaywi [46], who studied the difficulties of translating English business vocabulary using experimental material. Alolaywi's study concludes that a certain number of errors in the translation of BC is acceptable.…”
Section: Discussionsupporting
confidence: 87%
“…These advancements encompass various aspects, including the integration of translation theory into practical courses, the adoption of translanguaging as a teaching method, and a heightened emphasis on the importance of translation abilities in response to market demands Arab World English Journal for Translation & Literary Studies ISSN: 2550-1542 | www.awej-tls.org 108 (Alwazna, 2023;Abdellah, 2023). Research has indicated that training programs incorporating simulated work situations have proven successful in enhancing translation abilities and increasing participant satisfaction levels (Alolaywi, 2022). Additionally, there is a growing focus on training translators based on their skills and recognizing the unique teaching abilities required for translator trainers to maintain high teaching standards in a rapidly evolving job market (Pierre Najm & Abou Fadel Saad, 2022).…”
Section: Recent Developments In the Fieldmentioning
confidence: 99%
“…There is an impressive number of scientific works published on the preparation of future translators and the developing of their practical skills (Alolaywi, 2022;Coban, 2015;Davies, 2012;Tian, 2020;Gile, 2009;González Pym, 2014). Using advertising slogans can be a helpful tool in preparing future translators by helping them to develop skills in interpreting and translating catchy phrases and slogans that are often used in marketing and advertising.…”
Section: Introductionmentioning
confidence: 99%